COVID-19 impact on technical and vocational education and training in Sri Lanka. - Hayashi, Ryotaro; Asian Development Bank (Manila,Philippines Asian Development Bank, [2021])
Prior to the pandemic, there was an adoption rate of 36% for online learning in Sri Lanka. The brief notes that 60%-70% of major TVET courses continued via online learning since the COVID-19 outbreak. However, the quality of learning could drop significantly due to difficulty in conducting practical training online and the lack of internet access and digital devices. In addition, TVET graduates in the tourism and hospitality sector as well as self employed TVET graduates have been the hardest hit.
Keywords: Education -- Sri Lanka; Technical,Vocational education -- Sri Lanka; COVID-19.; Electronic book